2009
DOI: 10.2174/156802609788085296
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cancer Uses of Histone Deacetylase Inhibitors: Effects on Infectious Diseases and β-Hemoglobinopathies+

Abstract: After the approval of suberoylanilide hydroxamic acid (SAHA, vorinostat, Zolinza) for the treatment of cutaneous T cell lymphoma (CTCL), a number of HDAC inhibitors (HDACi) are currently in Phase II or III clinical trials (alone or in combination) for the treatment of a great number of tumors. In addition to these cancer uses, HDACi can be successfully used in non-cancer diseases. In this review we focused on the uses of HDACi in some infectious diseases and beta-hemoglobinopaties. In C. albicans cultures, HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 118 publications
(199 reference statements)
1
44
0
Order By: Relevance
“…HDACis exhibit promise in the treatment of cancer and certain parasitic and viral infections. 14,109 The HDACis include trichostatin A (TSA), romidepsin/depsipeptide, suberoylanilide hydroxamic acid (SAHA; vorinostat), panobinostat and MG-CD0103 (mocetinostat). However, only SAHA and romidepsin are licensed for clinical use (for cutaneous T cell lymphoma).…”
Section: Hdacismentioning
confidence: 99%
See 3 more Smart Citations
“…HDACis exhibit promise in the treatment of cancer and certain parasitic and viral infections. 14,109 The HDACis include trichostatin A (TSA), romidepsin/depsipeptide, suberoylanilide hydroxamic acid (SAHA; vorinostat), panobinostat and MG-CD0103 (mocetinostat). However, only SAHA and romidepsin are licensed for clinical use (for cutaneous T cell lymphoma).…”
Section: Hdacismentioning
confidence: 99%
“…However, only SAHA and romidepsin are licensed for clinical use (for cutaneous T cell lymphoma). 14,110,111 As HDACis potentiate the cytotoxicity of DNA methylation inhibitors (e.g., cisplatin, the anthracyclines, dexamethasone), they may be used together with these inhibitors. [109][110][111] Mammalian and fungal HDACs are substantially homologous and investigators have identified several classes and subclasses of HDACs in fungi (e.g., the class I enzymes RpdA and HosA, the class II enzymes HdaA and HosB).…”
Section: Hdacismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators had already identified that HDAC are required for chromatin condensation prior to enucleation of murine erythroblasts immortalized with the Friend virus. 12 Using primary normal cells, Ji et al confirmed these data by demonstrating that the HDAC inhibitors trichostatin A and valproic acid inhibit chromatin condensation of primary erythroblasts in culture. Using short interfering RNA technology, they then identified that the process of chromatin condensation is specifically dependent on HDAC2 activity while HDAC1, 3 and 5 are apparently dispensable (Figure 2).…”
Section: A Newly Identified Role For Histone Deacetylases In Erythropmentioning
confidence: 89%